Gastronomía típica e identidad turística en el cantón Vinces - Rivera Valle, Maria Elena (2019)
This research project shows the importance of typical gastronomy in the tourist identity of Canton Vinces, understanding the need to rescue Tourism in the Canton by training those involved in tourism-related issues. Vinces, over the years, has become consolidated as a tourist area not only in the Province of Los Ríos but also in Ecuador, the same as for its great diversity of tourist attractions, attracts its own and strangers to visit it and fall in love with its culture , its environment, its beaches, its forests, etc. Vinces, has the Abras de Mantequilla, which is located in the upper basin of the Guayas River, on March 14, 2000 it was declared a Ramsar site, so it was also declared in 2005 as an area of importance for conservation bird's. Vinces also has beautiful beaches and a river of fresh water, the same one that in 1968 was declared “the first freshwater resort in Ecuador”, which is why it attracted thousands of tourists who came from all over the world. Country to enjoy its rich waters and share pleasant moments with family and friends. For the aforementioned it is possible to appreciate the tourist wealth of this canton, however this must be accompanied by other factors that give it the plus that it needs to continue growing, among them, culture, history and one of the most important, the typical gastronomy of the area. The Canton Vinces has a gastronomy that attracts many tourists, for its exquisite typical dishes such as: seco de pollo, seco de pato, bollos, muchines, ayampacos, guisos de pescado, caldo de bolas, humitas, tamales, hayacas, Among many dishes more than being well exploited allow to help in the local economy, allowing the work of hundreds of families dedicated to the gastronomy business. But despite all the tourist potential that Vinces has, gastronomy has been changing in the canton, entering dishes that are not typical of the area, without seeing the evil that is done to the culinary culture of the canton, losing Little by little his tourist identity. That is why the present project seeks to incentivize the Vincenian community dedicated to the sale of food, to recover the tourist identity of the canton, recognizing the importance of its typical gastronomy, to be able to show the tourist the Vincenian gastronomic culture, as it has existed since many years ago, and that is for herself that Vinces earned her space in history as a city rich in tourism